Formulation Development and Evaluation of Mucoadhesive Buccal Tablets of Acebutolol Hydrochloride - Chaudhari, Priyanka Dilip; Deore, Amol Bhalchandra; Jagtap, Manoj Jagannath; Gupta, Devanshi Sunil (Asian Journal of Pharmaceutical Research and Development, 2022)
A mucoadhesive drug delivery system is an oral dosage form, where the tablet, gel, or patch is attached to the buccal region for direct absorption of the drug into blood circulation. This dosage form has been employed to improve the bioavailability of drugs that undergoes significant hepatic first-pass metabolism. Acebutolol is a beta sympatholytic agent used to treat high blood pressure and irregular heartbeat (arrhythmia). Lowering high blood pressure helps prevent strokes, heart attacks, and kidney problems. In present investigation, mucoadhesive buccal tablets of acebutolol HCl were prepared using carbopol 940 in varying concentrations with secondary polymer xanthan gum by direct compression method. Nine batches were prepared as per 32 factorial designs, to investigate the combined effects of independent variables namely carbopol 940 and xanthan gum on dependant variables namely swelling index, mucoadhesion strength and in-vitro drug release using design expert software version 8.0.7.1. Preformulation studies confirmed the identity and purity of the drug by means of UV spectroscopy, IR spectroscopy, DSC analysis, and melting point determination. The tablets were evaluated for hardness, thickness, weight variation, friability, and drug content concluded that all these parameters were in an acceptable range of pharmacopoeial specification. The buccal tablets were studied for surface pH, swelling index, in vitro drug release study, adhesion force, in vitro mucoadhesive strength, stability, and compatibility study to optimise the formula. Amongst all factorial batches (F1 to F9), batch F5 (30 mg carbopol 940 and 30 mg xanthan gum) showed maximum drug release of 99.96 % after 12 hr of study and also showed better contact with biological membrane. The drug release kinetics of batch F5 was found to be best fitted to zero order kinetic model and exhibited anomalous diffusion release mechanism. The formulation F5 exhibited good correlation (R2=0.992) for in-vitro drug release. All the evaluation parameters give positive results and comply with the standards. Stability studies were carried out on the developed formulations indicating that the formulations were stable during the period of 6 months. In conclusion, the formulation F5 is stable and effective for quick action and seems to be alternative to the conventional tablet.